Does Dog Ownership Affect the Owners' Quality of Motivation to Engage in Physical Activity? - Frueauf, Courtney (East Carolina University, 2012)
Using the framework of the self-determination theory (SDT), the current study compared men and women dog owners' and non-dog owners' a) physical activity levels, b) perceived competence, autonomy, and relatedness during physical activity, tested c) the correlations between dog ownership and self-determined motivation to engage in physical activity, and d) the roles of age, gender, and marital status on the relationship between dog ownership and self-determined motivation to be active. 223 volunteers participated in a cross sectional internet survey inquiring about physical activity, self-determined motivation, competence, autonomy, and relatedness, and activity completed with a pet dog(s). Results obtained using t tests revealed that dog owners have higher perceived relatedness during physical activity than non-dog owners (p<0.001). The relationship between dog walking and self-determined motivation of dog owners was assessed by conducting a correlation analysis. Total dog walking completed by dog owners was negatively correlated with amotivation, r=-0.188, n=113, p<0.05, positively correlated with identified regulation, r= 0.384, n=113, p<0.01, intrinsic motivation, r=0.302, n=113, p<0.01, and competence. This suggests an increase in dog walking leads to a decrease in amotivation but leads to an increase in identified regulation motivation; higher quality self-determined motivation. The more competent owners feel about walking and/or walking with a dog, the more likely they are to increase dog walking time. Enhancing perceived competence about physical activity and proper dog ownership may promote more dog walking in communities and more physical activity overall.
Keywords: Kinesiology; Health sciences; Dog ownership; Dog walking; Physical activity; Relatedness; Self-determination theory; Self-determined motivation; Dog owners--Psychology; Dog owners--Research; Exercise--Psychological aspects